2020
DOI: 10.1186/s12884-020-02863-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal outcomes and determinants of iodine deficiency in third trimester of pregnancy in an iodine sufficient area

Abstract: Background: Mild to moderate iodine deficiency in pregnant women may expose them to the increased risk of the development of goiter and thyroid disorder. There is a relationship between low maternal UIC (Urinary iodine concentration) in pregnancy and diminished placental weight and neonatal head circumference. The current study was an attempt to assess iodine nutritional status, its determinants and relationship with maternal and neonatal outcomes. Methods: In this population based cross-sectional study, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The women who assured the requisite pre-gestational iodine intake with foods presented a lower rate of spontaneous miscarriage, and a lower rate of the composite variable of adverse materno-fetal events than those who did not. Iodine deficiency during pregnancy has been found to be related with materno-fetal complications, such as higher rates of Neonatal Intensive Care Unit (NICU) admissions and preterm delivery [47]. Moderate iodine deficiency is associated with a higher risk of miscarriage, preterm labor and low birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…The women who assured the requisite pre-gestational iodine intake with foods presented a lower rate of spontaneous miscarriage, and a lower rate of the composite variable of adverse materno-fetal events than those who did not. Iodine deficiency during pregnancy has been found to be related with materno-fetal complications, such as higher rates of Neonatal Intensive Care Unit (NICU) admissions and preterm delivery [47]. Moderate iodine deficiency is associated with a higher risk of miscarriage, preterm labor and low birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we also found a rate of 16% of preterm birth in farmers. According to Gargari research, iodine deficiency in pregnant women increases the risk of premature birth 3.3-fold [ 37 ]. Government iodination programs using iodized salt are encouraged, and iodized salt is inexpensive and easy to obtain in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Dineva et al (78) reported that there was a positive association of maternal age with UI/Creat; however, the relationship may be confounded by the association of maternal age with dietary patterns and iodine-supplement use. In the study by Gargari et al (83) , other factors such as whether the pregnancy was planned, the time since the most recent pregnancy, maternal education level and maternal iodine supplement use prior-to and during pregnancy were associated with better iodine status.…”
Section: Iron Iodine and Vitamin D Deficiency In Pregnancy 293mentioning
confidence: 90%
“…The setting is also an important factor to consider in interpreting the relationship between body weight and iodine status. In a study of Iranian women by Gargari et al (83) , the odds of UIC <150 μg/l decreased by 13 % for every 1 kg increase in weight during pregnancy, which the authors posit was a proxy indicator of dietary quality.…”
Section: Iron Iodine and Vitamin D Deficiency In Pregnancy 293mentioning
confidence: 99%